Ma’had Internasional: Integrasi Agama-Sains Berbasis Moderasi Islam - Syarif, Zainuddin; Thabrani, Abdul Mukti (Islamika Inside: Jurnal Keislaman dan Humaniora, 2019)
Abstract: The study of the integration of religion and science always attracts the attention of many people, especially academics in religious tertiary circles. Theoretically, the discourse is intended to bridge the meeting of religion-science, which in many occasions is often disputed. To the extent that there are many ideas on the integration of religion and science, at both the theoretical and practical levels, one of them is the idea of ​​establishing an international ma'had. This study will specifically examine the idea of ​​the integration of Islam-based moderation of Islam in Islamic religious tertiary institutions through Ma'had International. Three main issues that will be the focus of the study, namely: the concept of international ma'ad, the integration of religion-science, and finally, the moderation of Islam. Three focus of study will be translated into two research questions, namely; 1) What is meant by the concept of International ma'had and Islamic moderation? 2) What is the role and strategic function of the international ma'had in integrating Islamic moderation-based religions? This study is a literature study based on the type of qualitative research. The data used in the study are secondary data sourced from library data. The theoretical perspective used is John F. Haught's theory of religious integration. Theoretically, this study has a major contribution in enriching the science of religion, especially the study of integration of religion and science. in practice, this study has a major contribution in terms of providing solutions to the ideal idea of ​​integrating Islamic moderation-based religion in the environment of Islamic religious colleges. The findings of this study contain an in-depth explanation of the concept of ma'had International, as well as an in-depth analysis of the integration strategy of Islam-based moderation based Islam through the idea of ​​ma'had International within the Islamic diversity tertiary environment.